2015
DOI: 10.1002/hep.28289
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hedgehog signaling ameliorates hepatic inflammation in mice with nonalcoholic fatty liver disease

Abstract: Hedgehog (Hh)-signaling plays a critical role in liver development, regeneration, injury repair and carcinogenesis. Activation of Hh signaling has been observed in patients with nonalcoholic fatty liver diseases (NAFLD); however, the pathobiological function and regulatory mechanism of hepatic Hh signaling in the pathogenesis of NAFLD remain to be further defined. This study was designed to examine the effect and mechanism of hepatic Hh signaling in high fat diet (HFD)-induced NAFLD by using pharmacological Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 42 publications
(108 reference statements)
2
75
0
Order By: Relevance
“…Hepatocytes also express components of the hedgehog signaling cascade, e.g., plasma membrane receptor smoothened, and may represent an important target of hedgehog signaling during lipotoxicity (51). Activation of Gli1, a transcription factor mediating canonical hedgehog signaling, increased production of osteopontin by hepatocytes, which in turn promoted macrophage-associated proinflammatory response in a paracrine fashion (124). Finally, inhibition of hedgehog signaling by pharmacological inhibitors of smooth ened (vismodegib and erismodegib) or genetic deletion of smoothened in the liver parenchyma prevents liver injury, inflammation, and fibrosis in mouse models of NAFLD and NASH (51,124).…”
Section: Free Fatty Acid-induced Tlr and Nf-b Activationmentioning
confidence: 99%
“…Hepatocytes also express components of the hedgehog signaling cascade, e.g., plasma membrane receptor smoothened, and may represent an important target of hedgehog signaling during lipotoxicity (51). Activation of Gli1, a transcription factor mediating canonical hedgehog signaling, increased production of osteopontin by hepatocytes, which in turn promoted macrophage-associated proinflammatory response in a paracrine fashion (124). Finally, inhibition of hedgehog signaling by pharmacological inhibitors of smooth ened (vismodegib and erismodegib) or genetic deletion of smoothened in the liver parenchyma prevents liver injury, inflammation, and fibrosis in mouse models of NAFLD and NASH (51,124).…”
Section: Free Fatty Acid-induced Tlr and Nf-b Activationmentioning
confidence: 99%
“…Hedgehog signalling is inhibited in healthy liver but activated in disease; ballooned hepatocytes produce the Hedgehog ligand sonic hedgehog, which stimulates hepatic stellate cells and fibroblasts, initiating a profibrotic response 237 . Inhibiting or eliminating smoothened, a G proteincoupled receptor mediating signalling in the presence of sonic hedgehog ligand 238 , resulted in reduced macrophage activation and expression of proinflammatory genes in a mouse model 239 . Analysis of liver biopsies from patients with NASH enrolled in the PIVENS trial showed that response to treatment (vitamin E) was inversely associated with levels of sonic hedgehog 240 .…”
Section: Targeting the Gut–liver Axismentioning
confidence: 99%
“…21 Likewise, liver-specific deletion of smoothened attenuates liver inflammation in high fat diet-fed mice. 22 Interestingly, in patients with NASH enrolled in the PIVENS trial, improvement in liver injury correlated with a decreased number of Shh-positive hepatocytes. On the other hand, a reduction of Shh-positive hepatocytes was not associated with improvement of fibrosis in these patients.…”
Section: Sublethal Lipotoxic Hepat Ocyte Injurymentioning
confidence: 99%